Differential Protein Contents in Two Members of the Whitefly Bemisia tabaci (Hemiptera: Aleurodidae) Complex: Reproductive and Invasive Implications - Dieng, Hamady; Ahmad, Abu Hassan; Satho, Tomomitsu; Salmah, R. Che; Aziz, A. Thabani; Miake, Fumio; Vargas, R.E. Morales; Morales, P.; Ahmad, H.; Saad, A. Ramli; Rajen, S.; Abu Bakar, S. (Maxwell Scientific Organization, 2012)
Although the displacement of some native whitefly species by the B biotype of Bemisia tabaci has been noted in China, it is still unclear which physiological and molecular mechanisms predominate during such invasions. Here, we investigated proteome variability in both B biotype and the native ZHJ1 haplotype. ZHJ1 eggs showed larger numbers of specific proteins than B eggs. A set of proteins found in B eggs were present at higher levels in ZHJ1. Three ZHJ1 egg proteins were present at higher levels in B eggs. ZHJ1 males possessed four specific proteins, and at least five other male proteins were shared by the two whiteflies. Two proteins identified in ZHJ1 males were present at higher levels in B males. Three other shared male proteins were found at much higher levels in ZHJ1 than in the B biotype. Both ZHJ1 and B expressed three specific female proteins. Most of the female proteins identified in ZHJ1 were present at much higher levels in B. In conclusion, protein content indexed by electrophoretic profiling has likely played an important role during the displacement of natives by the B biotype.